Desenvolvimento de método cromatográfico para quantificação dos níveis de poliaminas e investigação da formação de adutos com naftoquinonas - Figueiredo, Eugenia Abrantes de (2014)
Polyamines are aliphatic organic bases belonging to the group of bioactive amines that have important metabolic and physiological functions in animals, plants and microorganisms. Amongst the most important polyamines biologically are spermidine [N-(3-aminopropyl) -1,4-butane diamine or tetramethylene diamine-aminopropyl] (SPD) and spermine [N, N'-bis (3-aminopropyl) -1,4-butane diamine or diaminopropil-tetramethylethylenediamine] (SPM). Polyamines are intimately involved in the growth and replication of many cell types, and it has been demonstrated that they are found in high concentrations in rapid growing cells. It is possible that substances such as naphthoquinones, which can react with polyamines have the ability to block its function by depleting its concentration. The direct detection of polyamines by HPLC with UV detection is hampered because they lack structural groups with high molar absorptivity. Thus, the objective of this study was to develop and validate a chromatographic method using fluorescence detection that could be applied for quantifying the cellular levels of polyamines in cell cultures based on the following parameters: selectivity, linearity, precision and accuracy. The polyamines were derivatized pre-column with dansyl chloride and were detected by fluorescence (ex= 365 nm; em= 510 nm) using a chromatographic method using gradient elution with a mobile phase consisting of methanol: water (35-95 v/v), a reversed-phase C18 column (250 x 4.6 mm, 5μm) at a flow rate of 1.0 mL/min., in 35 minutes. The chromatographic method was validated according to Resolution 899 recommended by the National Sanitary Agency of Brazil (ANVISA), and was linear in the concentration range used for SPD (0.0097 to 0.97 pmol/mL) and SPM ( 0.074 to 0.74 pmol/mL), precise (≤ 15% for medium and high concentrations, ≤ 20% for the low concentration), exact for SPD (97-118%) and SPM (92-119%), It also showed selectivity (demonstrated by separation of polyamines and proteins present in cell culture medium). The developed method was also applied to the analysis of polyamines incubated with the naphtoquinones (lapachol and β-lapachone). The concentration of these polyamines was depleted when incubated for 17 hours at ambient temperature (decrease of 67% and 50% for SPD and SPM levels respectively when incubated with lapachol and a decrease of 44% and 37,5% for SPD eand SPM when incubated with β-lapachona). These results demonstrate that the developed method is adequate for the analysis of polyamines in cell culture and that a probable mechanism of antitumoral action for the naphtoquinones may involve the formation of adducts with polyamines